The Influence of Taste, Service Quality, and Business Location on Customer Satisfaction at Warung Wardani in Denpasar City - Anak Agung Putu Dicha Widnyana Putra; I Made Jatra (International Journal of Management Research and Economics, 2025)
Customer Satisfaction is a feeling that arises from the comparison between the performance of a product or service with the expectations held by the customer. When customers are satisfied with the taste, quality of service, and location of the business, customer satisfaction can be increased. This study aims to determine the effect of taste, quality of service, and location of the business on customer satisfaction at Warung Wardani in Denpasar City. The location of this study was at Warung Wardani at Jalan Yudistiran No. 2. The method chosen for gathering data was a questionnaire.The subjectssurveyed were clients who had frequented Warung Wardani, with a total of 112 individuals participating. The techniques employed for data analysis included Descriptive Statistical Analysis, Data Instrument Testing, Classical Assumptions, Multiple Linear Regression, along with t, F, Determination, and Beta Coefficient evaluations. The findings revealed that taste significantly and positively influences customer satisfaction, that Service Quality also significantly and positively affects customer satisfaction, and that Location contributes positively and significantly to customer satisfaction. The researcher recommends that Warung Wardani should continue to promote its image as a provider of tasty food, enhance service quality, and select a strategic location. This approach is seen as a strong method for boosting customer satisfaction and enticing customers to make repeat purchases. A key strategic takeaway from this research is that Warung Wardani could enhance its competitive edge by expanding its parking facilities.